Tunable 3D Extended Self‐Assembled Gold Metamaterials with Enhanced Light Transmission. (3rd April 2013) - Salvatore, Stefano; Demetriadou, Angela; Vignolini, Silvia; Oh, Sang Soon; Wuestner, Sebastian; Yufa, Nataliya A.; Stefik, Morgan; Wiesner, Ulrich; Baumberg, Jeremy J.; Hess, Ortwin; Steiner, Ullrich
<x xml:space="preserve">Abstract</x> The optical properties of metamaterials made by block copolymer self‐assembly are tuned by structural and environmental variations. The plasma frequency red‐shifts with increasing lattice constant and blue‐shifts as the network filling fraction increases. Infiltration with dielectric liquids leads also to a red‐shift of the plasma edge. A 300 nm‐thick slab of gyroid‐structured gold has a remarkable transmission of 20%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>